De originaliteit van het plagiaat. Gimmick! eigent zich op postmoderne wijze postmoderne beeldende kunst toe - Gielen, Albert (Acta Neerlandica, 2021)
Gimmick! written by Joost Zwagerman is a postmodern artist’s novel. The protagonist Walter van Raamsdonk, in short called Raam, is a visual artist, just like his friends Groen and Eckhardt. This article analyzes the novel as a postmodern phenomenon centered on postmodern visual art. Because the novel and the visual arts in the novel can be characterized as postmodern, it is investigated which characteristics of the postmodern can be found in both disciplines. To what extent does the novel reflect post-modern art? Citing in both disciplines has far-reaching consequences for the appearance of visual art and for the novel.